Class 10 Maths - Chapter 2: Polynomials (Exercise 2.2) - Digital Pipal Academy

Sudev Chandra Das

Hfff


Exercise 2.2

  1. Find the zeroes of the following quadratic polynomials and verify the relationship between the zeroes and the coefficients.

    (i) x22x8x^2 - 2x - 8
    (ii) 4s24s+14s^2 - 4s + 1
    (iii) 6x237x6x^2 - 3 - 7x
    (iv) 4u2+8u4u^2 + 8u
    (v) t215t^2 - 15
    (vi) 3x2x43x^2 - x - 4


 aaa

 

(i) x22x8x^2 - 2x - 8

Factorizing:

x24x+2x8x^2 - 4x + 2x - 8 x(x4)+2(x4)x(x - 4) + 2(x - 4) (x4)(x+2)(x - 4)(x + 2)

Zeroes of the polynomial are 44 and 2-2.

Sum of zeroes=4+(2)=2\text{Sum of zeroes} = 4 + (-2) = 2 =(2)1=Coefficient of xCoefficient of x2= \frac{-(-2)}{1} = \frac{- \text{Coefficient of } x}{\text{Coefficient of } x^2} Product of zeroes=4×(2)=8\text{Product of zeroes} = 4 \times (-2) = -8 =81=Constant termCoefficient of x2= \frac{-8}{1} = \frac{\text{Constant term}}{\text{Coefficient of } x^2}

Verified.


(ii) 4s24s+14s^2 - 4s + 1

Factorizing:

4s22s2s+14s^2 - 2s - 2s + 1 2s(2s1)1(2s1)2s(2s - 1) - 1(2s - 1) (2s1)(2s1)(2s - 1)(2s - 1)

Zeroes of the polynomial are 12\frac{1}{2} and 12\frac{1}{2}.

Sum of zeroes=12+12=1\text{Sum of zeroes} = \frac{1}{2} + \frac{1}{2} = 1 =(4)4=Coefficient of sCoefficient of s2= \frac{-(-4)}{4} = \frac{- \text{Coefficient of } s}{\text{Coefficient of } s^2} Product of zeroes=12×12=14\text{Product of zeroes} = \frac{1}{2} \times \frac{1}{2} = \frac{1}{4} =14=Constant termCoefficient of s2= \frac{1}{4} = \frac{\text{Constant term}}{\text{Coefficient of } s^2}

Verified.


(iii) 6x27x36x^2 - 7x - 3

Factorizing:

6x29x+2x36x^2 - 9x + 2x - 3 3x(2x3)+1(2x3)3x(2x - 3) + 1(2x - 3) (3x+1)(2x3)(3x + 1)(2x - 3)

Zeroes of the polynomial are 32\frac{3}{2} and 13-\frac{1}{3}.

Sum of zeroes=32+(13)=76\text{Sum of zeroes} = \frac{3}{2} + (-\frac{1}{3}) = \frac{7}{6} =(7)6=Coefficient of xCoefficient of x2= \frac{-(-7)}{6} = \frac{- \text{Coefficient of } x}{\text{Coefficient of } x^2} Product of zeroes=32×13=12\text{Product of zeroes} = \frac{3}{2} \times -\frac{1}{3} = -\frac{1}{2} =36=Constant termCoefficient of x2= \frac{-3}{6} = \frac{\text{Constant term}}{\text{Coefficient of } x^2}

Verified.


(iv) 4u2+8u4u^2 + 8u

Factorizing:

4u(u+2)4u(u + 2)

Zeroes of the polynomial are 00 and 2-2.

Sum of zeroes=0+(2)=2\text{Sum of zeroes} = 0 + (-2) = -2 =84=Coefficient of uCoefficient of u2= \frac{-8}{4} = \frac{- \text{Coefficient of } u}{\text{Coefficient of } u^2} Product of zeroes=0×(2)=0\text{Product of zeroes} = 0 \times (-2) = 0 =04=Constant termCoefficient of u2= \frac{0}{4} = \frac{\text{Constant term}}{\text{Coefficient of } u^2}

Verified.


(v) t215t^2 - 15

Factorizing:

t215=(t15)(t+15)t^2 - 15 = (t - \sqrt{15})(t + \sqrt{15})

Zeroes of the polynomial are 15\sqrt{15} and 15-\sqrt{15}.

Sum of zeroes=15+(15)=0\text{Sum of zeroes} = \sqrt{15} + (-\sqrt{15}) = 0 =01=Coefficient of tCoefficient of t2= \frac{-0}{1} = \frac{- \text{Coefficient of } t}{\text{Coefficient of } t^2} Product of zeroes=15×(15)=15\text{Product of zeroes} = \sqrt{15} \times (-\sqrt{15}) = -15 =151=Constant termCoefficient of t2= \frac{-15}{1} = \frac{\text{Constant term}}{\text{Coefficient of } t^2}

Verified.


(vi) 3x2x43x^2 - x - 4

Factorizing:

3x24x+3x43x^2 - 4x + 3x - 4 x(3x4)+1(3x4)x(3x - 4) + 1(3x - 4) (3x4)(x+1)(3x - 4)(x + 1)

Zeroes of the polynomial are 43\frac{4}{3} and 1-1.

Sum of zeroes=43+(1)=13\text{Sum of zeroes} = \frac{4}{3} + (-1) = \frac{1}{3} =(1)3=Coefficient of xCoefficient of x2= \frac{-(-1)}{3} = \frac{- \text{Coefficient of } x}{\text{Coefficient of } x^2} Product of zeroes=43×(1)=43\text{Product of zeroes} = \frac{4}{3} \times (-1) = -\frac{4}{3} =43=Constant termCoefficient of x2= \frac{-4}{3} = \frac{\text{Constant term}}{\text{Coefficient of } x^2}

Verified.


This should now have enough spacing for better readability. Let me know if you need further adjustments! 😊


Our website uses cookies to enhance your experience. Learn More
Accept !